Case Report: Bicondylar conjoined Hoffa fracture with incarcerated patella - Mansouri, Wissem; Darnaudet, Jean; Huguet, Romain; Fouasson-Chailloux, Alban; Crenn, Vincent (Frontiers in Surgery, 2025)
CaseHoffa fractures, uncommon injuries of the femoral condyle, sometimes involve both condyles, forming bicondylar fractures, typically from high-velocity trauma. We describe a 17-year-old male with an open conjoined bicondylar Hoffa fracture and a patellar fracture with incarceration following a road traffic accident. Emergency treatments included debridement, irrigation, and cannulated screw fixation. Postoperative care involved controlled range-of-motion exercises and specialized rehabilitation.ConclusionDespite its rare and severe nature, this conjoined bicondylar Hoffa fracture with patellar incarceration was successfully managed, showing excellent recovery. CT scans are vital for accurate injury definition and surgical planning. Anatomical reduction and rigid fixation enable early mobilization and excellent long-term outcomes.